Sugar and slaves : the rise of the planter class in the English West Indies, 1624-1713 - Dunn, Richard S. (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia, by the University of North Carolina Press, 2000)
Sugar and Slaves presents a vivid portrait of English life in the Caribbean more than three centuries ago. Using a host of contemporary primary sources, Richard Dunn traces the development of plantation slave society in the region. He examines sugar production techniques, the vicious character of the slave trade, the problems adapting English ways to the tropics, and the appalling mortality rates for both blacks and whites that made these colonies the richest, but in human terms the least successful, in English America.